Implementasi E-Commerce Penjualan Batik Tulis Khas Pati Berbasis Website (Studi Kasus Batik Tulis Jengdur) - Monicasari, Lisa; Listyorini , Tri; Supriyati , Endang (Yayasan Literasi Sains Indonesia, 2023)
Website design from the implementation of E-Commerce implementation of the sale of typical pati hand-written batik which is expected to promote the sharing of information regarding product prices and product details of this typical pati hand-written batik quickly and is also the most popular choice. Currently, sales of typical Pati hand-drawn batik still use conventional methods, namely selling in shops and participating in exhibitions held in the city of Pati. This research was conducted using the waterfall method approach. Data collection was carried out using interviews and surveys at the Pati batik location. The use of this website is intended to increase the reach of product advertising without being limited by the availability of systems to increase sales. This online transaction system was created using Visual Studio Code as the material for creating an E-Commerce application for the sale of typical Pati batik, using the PHP programming language and MySQL as the database. This system is equipped with a payment feature using the Midtrans payment gateway, which still uses the sandbox version. This sales system is also equipped with a postage king API, which can provide information regarding shipping expeditions and shipping costs that must be paid by the buyer. The result of this research is a website-based online sales system and aims to develop the Pati hand-written batik business.